2015
DOI: 10.1097/scs.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Injury Mechanisms on Patterns and Management of Facial Fractures

Abstract: Mechanisms causing facial fractures have evolved over time and may be predictive of the types of injuries sustained. The objective of this study is to examine the impact of mechanisms of injury on the type and management of facial fractures at our Level 1 Trauma Center. The authors performed an Institutional Review Board-approved review of our network's trauma registry from 2006 to 2010, documenting age, sex, mechanism, Injury Severity Score, Glasgow Coma Scale, facial fracture patterns (nasal, maxillary/malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…This finding is in accordance with other studies on fracture occurrence. Morris et al 8 and Greathouse et al 9 reported a 5:1 and a 2.7:1 ratio in their studies, respectively. In particular, Al Ahmed et al 10 reported a huge bias against men with an 11:1 ratio, which may be due to ethnic characteristics in the UAE where social freedom for women is more restrictive than in other countries.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is in accordance with other studies on fracture occurrence. Morris et al 8 and Greathouse et al 9 reported a 5:1 and a 2.7:1 ratio in their studies, respectively. In particular, Al Ahmed et al 10 reported a huge bias against men with an 11:1 ratio, which may be due to ethnic characteristics in the UAE where social freedom for women is more restrictive than in other countries.…”
Section: Discussionmentioning
confidence: 88%
“…8 Although previous literature shows that the rate of facial fractures from MVA is decreasing due to new safety methods in cars, such as airbags and seatbelts, the protective effect is far less for nasal fractures. 1,28,31,32 Mouzakes et al suggested that airbags alone may even pose an increased risk of nasal fractures. 33 However, the majority of literature suggests that airbags and seat belts are paramount to injury prevention, especially the reduction of significant morbidity and mortality overall.…”
Section: Discussionmentioning
confidence: 99%
“…6 Greathouse et al evaluated all operations performed across three Level I trauma centers and one independent surgical center for trauma patients with facial fractures and found that 25.2% of patients with nasal fractures received surgical intervention at a mean of 8.9 days following injury. 1 They also included operations after discharge, while the NTDB only includes operations on the index hospitalization. Since our average hospital LOS was 6.9 days (i.e., longer than would be expected for nasal fracture alone) and due to the lack of follow-up data, our study did not capture all patients who eventually received treatment for their fracture at a later date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the general adult population, the primary mechanisms of facial fractures are motor vehicle accidents, assault, and falls. 7,8 However, assault has increasingly become the primary mechanism of facial fractures in U.S. urban centers such as Detroit, Boston, and Chapel Hill. 911 Common types of facial fractures in the general population include nasal bone, mandible, and mala/maxilla fractures.…”
Section: Introductionmentioning
confidence: 99%